In vitro Evaluation of Surface Free Energy of Dentin after Treatment with Sodium Trimetaphosphate Associated or Not with Fluoride, Exposed or Not to Calcium - Oliveira, Lenara Queiroz Chaves [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Morais, Leonardo Antônio de [UNESP]; Gonçalves, Silvio César [UNESP]; Souza, José Antonio Santos; Pedrini, Denise [UNESP] (Karger Publishers, 2022)
It has been stated that sodium trimetaphosphate (TMP) promotes a more anionic dentin surface inducing greater calcium (Ca) and phosphate precipitation. The aim of the present study was to evaluate in vitro the surface free energy (γs) of dentin after treatment with TMP associated or not with fluoride (F), exposed or not to Ca, as well as the adsorption of TMP, F, and Ca by dentin. Bovine dentin blocks (n = 12 blocks/group) were treated with solutions containing TMP at 0, 1, 3, or 9 (w/v) followed or not by the application of Ca. These solutions were or were not associated to 1,100 ppm F. F, Ca, and TMP were determined in the solutions before and after the treatment to calculate the adsorption by dentin. To analyze the γs of dentin, the apolar (γsLW), and polar (γsAB), components were determined by contact angle measurement. Data were submitted to 2-way ANOVA followed by the Student-Newman-Keuls test (p < 0.05). TMP reduces γs of dentin and increases electron donor sites (γs-). Higher values of γs- led to higher adsorption of Ca (p < 0.001). The F/TMP association did not change γs or γsLW and reduced the values of γs-, but the adsorption of Ca was higher. There was correlation between the adsorption of TMP and γs- (Pearson's r = 0.801; p < 0.001) and F (Pearson's r = 0.871, p < 0.001). It is possible to conclude that TMP increased γs- and Ca adsorption, and reduced γs. The association with F increased the adsorption of TMP without rising γs-; however, there was higher adsorption of Ca.
Keywords: Dentin; Energy; Fluorides; Phosphates